Alcoholic and Non-Alcoholic Liver Diseases: Promising Molecular Drug Targets and their Clinical Development - Thapa, Komal; Grewal, Ajmer S.; Kanojia, Neha; Rani, Lata; Sharma, Neelam; Singh, Sukhbir (Current Drug Discovery Technologies, 2021)
Alcoholic and non-alcoholic fatty liver diseases have become a serious concern worldwide. Both these liver diseases have an identical pathology, starting from simple steatosis to cirrhosis and, ultimately to hepatocellular carcinoma. Treatment options for alcoholic liver disease (ALD) are still the same as they were 50 years ago which include corticosteroids, pentoxifylline, antioxidants, nutritional support and abstinence; and for non-alcoholic fatty liver disease (NAFLD), weight loss, insulin sensitizers, lipid-lowering agents and anti-oxidants are the only treatment options. Despite broad research in understanding the disease pathophysiology, limited treatments are available for clinical use. Some therapeutic strategies based on targeting a specific molecule have been developed to lessen the consequences of disease and are under clinical investigation. Therefore, focus on multiple molecular targets will help develop an efficient therapeutic strategy. This review comprises a brief overview of the pathogenesis of ALD and NAFLD; recent molecular drug targets explored for ALD and NAFLD that may prove to be effective for multiple therapeutic regimens and also the clinical status of these promising drug targets for liver diseases.
Keywords: Alcoholic liver disease